2014
DOI: 10.5664/jcsm.3518
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Prospective Comparative Effectiveness Study of the Effect of Physician Certification and Center Accreditation on Patient-Centered Outcomes in Obstructive Sleep Apnea

Abstract: than those who did not receive such sleep specialist consultation. 8 Recently, a randomized controlled non-inferiority trial reported that treatment of OSA by primary care physicians was non-inferior to that of sleep specialists with regard to resolution Objectives: To study the effect of sleep center accreditation and Sleep Medicine board certifi cation of physicians on patient-centered outcomes in obstructive sleep apnea (OSA). Design: Prospective, multicenter, comparative effectiveness study. Setting: Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 30 publications
2
42
0
2
Order By: Relevance
“…Several studies have shown improved treatment compliance, greater patient satisfaction, and greater timeliness in patients treated at accredited sleep centers or by board-certified sleep medicine physicians. 69,70 As the delivery of health care continues to evolve, clinical assessment, diagnostic testing, and ongoing follow-up may occur using telemedicine approaches that incorporate HSAT and automatically adjusting PAP therapy. Such approaches may prove to increase access and improve convenience for CMVOs, while reducing costs.…”
Section: Qualifications or Credentials Necessary For Medical Practitimentioning
confidence: 99%
“…Several studies have shown improved treatment compliance, greater patient satisfaction, and greater timeliness in patients treated at accredited sleep centers or by board-certified sleep medicine physicians. 69,70 As the delivery of health care continues to evolve, clinical assessment, diagnostic testing, and ongoing follow-up may occur using telemedicine approaches that incorporate HSAT and automatically adjusting PAP therapy. Such approaches may prove to increase access and improve convenience for CMVOs, while reducing costs.…”
Section: Qualifications or Credentials Necessary For Medical Practitimentioning
confidence: 99%
“…Limitations of the work by Parthasarathy and companions 10 are largely adequately addressed in the manuscript. The study design was intended to limit participation to those patients having OSA without secondary confounding disorders.…”
mentioning
confidence: 98%
“…When properly aligned, sleep specialists and AASM accredited centers can positively influence outcomes. 19 However, there is a large segment of our population who has limited access to a sleep specialist. Accordingly, the Academy has started efforts to develop policies and best practices to standardize and appropriately promote telehealth sleep services.…”
mentioning
confidence: 99%